AN ANALYSIS OF HOW WOMEN’S STRUGGLE PORTRAYED FROM THE MAIN CHARACTER IN THE MOVIE “LITTLE WOMEN (2019)” - Bejo Sutrisno; Nadya Putri Nurhasanah; Budi Rachmawati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
This study aims to identify the struggle of women against the figure of Jo March in the movie Little Women (2019) with a feminist approach. The discovery of women’s struggles in this movie, as well as the struggles of Jo March, the main character, in pursuing her dream, are discussed in this research. The researcher used qualitative research in this research. There are two sources of data used to analyze the related issues, namely primary and secondary data sources. Primary data sources from the movie Little Women (2019) and other sources such as international journals, websites, previous research, and other articles. From the researchers’ analysis, there are two conclusions. First, there are problems faced by the main character related to gender stereotypes, such as that women should marry well. The second is the struggle of the main character to pursue her dream in the future, like when the main character cuts her hair to sell, even though hair is a woman's crown at that time.